A Review of the Incidence of Aflatoxin M1 in Raw Milk and its Economic Losses - Ahmadi, Sayed Arif (Journal of Natural Sciences – Kabul University, 2024)
Aflatoxins are hazardous fungal toxin that produces in sufficient moisture, heat and preservation unfit condition and could brought about serious hazards to consumer health. The aim of this study is the systematic review and its economic losses of the Aflatoxin M1 incidence in raw, pasteurized and UHT milk in the world. Articles, guidelines and specific databases such as SID, PubMed, Scirus, Elsevier, Science Direct and WHO sits were searched for related topics cited. Contamination in cold season was higher than heat season. Milk is one of the most complete foods and its contamination is serious risk for public health and have adverse effects on humans, animals, and crops that result in illnesses and economic losses. Notify Aflatoxin M1 reduction methods in milk and dairy products are necessary.